Pyridinium-2-carbaldoximes with quinolinium carboxamide moiety are simultaneous reactivators of acetylcholinesterase and butyrylcholinesterase inhibited by nerve agent surrogates. (1st January 2021) - Lee, Hyun Myung; Andrys, Rudolf; Jonczyk, Jakub; Kim, Kyuneun; Vishakantegowda, Avinash G.; Malinak, David; Skarka, Adam; Schmidt, Monika; Vaskova, Michaela; Latka, Kamil; Bajda, Marek; Jung, Young-Sik; et al.
Abstract: The pyridinium-2-carbaldoximes with quinolinium carboxamide moiety were designed and synthesised as cholinesterase reactivators. The prepared compounds showed intermediate-to-high inhibition of both cholinesterases when compared to standard oximes. Their reactivation ability was evaluated in vitro on human recombinant acetylcholinesterase ( hr AChE) and human recombinant butyrylcholinesterase ( hr BChE) inhibited by nerve agent surrogates (NIMP, NEMP, and NEDPA) or paraoxon. In the reactivation screening, one compound was able to reactivate hr AChE inhibited by all used organophosphates and two novel compounds were able to reactivate NIMP/NEMP- hr BChE. The reactivation kinetics revealed compound 11 that proved to be excellent reactivator of paraoxon- hr AChE better to obidoxime and showed increased reactivation of NIMP/NEMP- hr BChE, although worse to obidoxime. The molecular interactions of studied reactivators were further identified by in silico calculations. Molecular modelling results revealed the importance of creation of the pre-reactivation complex that could lead to better reactivation of both cholinesterases together with reducing particular interactions for lower intrinsic inhibition by the oxime.